1992
DOI: 10.1034/j.1399-3054.1992.860203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous gibberellin A4/7 on tracheid production, longitudinal growth and the levels of indole‐3‐acetic acid and gibberellins A4, A7 and A9 in the terminal shoot of Pinus sylvestris seedlings

Abstract: Gibberellin A4/7 (GA4/7) was applied twice weekly to 2‐year‐old Pinus sylvestris (L.) seedlings in each of two years, starting close to budbreak and ending after shoot elongation, but before cambial activity ceased. In 1988, the GA4/7 was injected into the 1987 terminal shoot (0, 0.2 or 2 mg seedling−1 application−1), while in 1990 it was applied as a soil drench (0, 10 or 50 mg seedling−1 application−1). In the 1988 experiment, GA4/7 treatment promoted diameter growth, and tended to increase both longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The analysis of gibberellic acid equivalents was performed according to Fujioka et al (1986), Cakmak et al (1989 and Wang et al (1992) with some modifications. The freeze-dried tissue samples (1 g) were ground to powder in liquid nitrogen and homogenized in 3 cm 3 of 100 % methanol.…”
Section: Extraction Purification and Determination Of Phytohormonesmentioning
confidence: 99%
“…The analysis of gibberellic acid equivalents was performed according to Fujioka et al (1986), Cakmak et al (1989 and Wang et al (1992) with some modifications. The freeze-dried tissue samples (1 g) were ground to powder in liquid nitrogen and homogenized in 3 cm 3 of 100 % methanol.…”
Section: Extraction Purification and Determination Of Phytohormonesmentioning
confidence: 99%
“…1), suggests that the effect of gibberellin on tracheid elongation is a cell-type-specific reaction which does not affect the rest of the tissue. Previous studies have shown a gibberellin effect on stem elongation (Wang et al, 1992 ;Little & Pharis, 1995), but these did not investigate the role of gibberellin on tracheid elongation. This specific effect on regenerated tracheid elongation is, therefore, different from the one reported by Aloni (1979), where gibberellin induced both primary phloem fibre elongation and also promoted maximal internode elongation under a high GA $ : low IAA ratio.…”
Section: mentioning
confidence: 99%
“…Little attention has been given to the possible role of gibberellin in tracheid differentiation (Little & Savidge, 1987). Wang et al (1992) reported that gibberellin, applied as a soil drench, caused an increase in tracheid number and stem elongation. However, the possible role of gibberellin in tracheid elongation was not studied by these workers.…”
Section: mentioning
confidence: 99%
“…Several GAs have been identified in the cambial region, and both endogenous and applied GAs have been found to be possibly related to stem radial increment (Aloni 1979(Aloni , 1988(Aloni , 1991Little and Savidge 1987;Wang et al 1992Wang et al , 1995Little and Pharis 1995). There has been one study reporting that applied gibberellin A 3 (GA 3 ) induced compression wood formation (Wardrop and Davies 1964).…”
Section: Gibberellinmentioning
confidence: 99%